2006
DOI: 10.1093/jac/dkl328
|View full text |Cite
|
Sign up to set email alerts
|

Once-daily tobramycin in cystic fibrosis: better for clinical outcome than thrice-daily tobramycin but more resistance development?

Abstract: The most important PK/PD parameter for clinical outcome in CF patients was C(max)/MIC. Outcome prediction of AUC(24)/MIC was dependent on the regimen. The increase of P. aeruginosa resistance after once-daily administration is linked to a long dosing interval. More and larger studies are needed to optimize the dosing regimen for maximum clinical outcome with minimum resistance development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 51 publications
7
100
0
Order By: Relevance
“…C max /MIC and AUC/ MIC ratios of 8 to 10 and 80 h to 100 h, respectively, are reasonable to predict the likelihood of efficacy in the treatment of nosocomial infections, including respiratory tract infections (217)(218)(219)(220). The most predictive PK/PD efficacy parameter in CF patients was the C max /MIC ratio (221).…”
Section: Preclinical and Clinical Pk/pd Studies In Cf Patientsmentioning
confidence: 97%
“…C max /MIC and AUC/ MIC ratios of 8 to 10 and 80 h to 100 h, respectively, are reasonable to predict the likelihood of efficacy in the treatment of nosocomial infections, including respiratory tract infections (217)(218)(219)(220). The most predictive PK/PD efficacy parameter in CF patients was the C max /MIC ratio (221).…”
Section: Preclinical and Clinical Pk/pd Studies In Cf Patientsmentioning
confidence: 97%
“…Once-and thrice-daily intravenous aminoglycoside therapy at the same daily dose were found to be equally effective clinically against pulmonary exacerbations of CF, but the emergence of resistance was not studied. 26,27 However, in a small clinical study in 33 patients with CF, tobramycin C max /MIC was found as the best predictor of clinical outcome as measured by lung function; 28 the investigators suggested that resistance was greater after once-daily dosing, but an alternative analysis may have led to a different conclusion. Recently we have shown that high ciprofloxacin concentrations for a short duration of exposure (at a specific fAUC/MIC) resulted in resistance prevention.…”
Section: Introductionmentioning
confidence: 99%
“…This likely reflects the availability of well-designed safety and efficacy studies and meta-analyses evaluating tobramycin EID in this population, and the lack of published research studies assessing the use of gentamicin and amikacin EID in those with CF. 10,11,[13][14][15][16][17][18] As in the pediatric CF population, empiric dosing of tobramycin was most commonly prescribed at 10 mg/kg/d. 19 This practice is consistent with the dose used in a large, randomized, controlled, noninferiority study published in 2005.…”
Section: Discussionmentioning
confidence: 99%
“…8 In light of the emergence of safety and efficacy data in the CF population, the Cystic Fibrosis Foundation deemed once-daily aminoglycoside dosing as acceptable for Pseudomonas aeruginosa (grade C recommendation) in its September 2009 pulmonary exacerbation guidelines. [9][10][11][12][13][14][15][16][17][18] A 2009 survey of United States pediatric CF centers and affiliate programs distributed after the publication of these guidelines reported the use of EID (with once-daily or twice-daily dosing) in the pediatric CF population to be 94%, a significant increase from previous reports. 19 While empiric evidence suggests the use of EID of aminoglycosides to be increasingly common in the United States CF population, the prevalence of EID use across United States adult CF centers as well as the dosing and monitoring practices associated with this regimen following publication of the CF pulmonary exacerbation guidelines remain to be elicited.…”
Section: Introductionmentioning
confidence: 99%